Resilience of the primary healthcare system: perspectives of German stakeholders at primary care interfaces during the second wave of the COVID-19 pandemic - Litke, Nicola; Weber, Sophia; Breckner, Amanda; Roth, Catharina; Peters-Klimm, Frank; Wensing, Michel; Stengel, Sandra (Frontiers in Medicine, 2024)
Worldwide, the primary care sector played a key role in coping the challenges of the SARS-CoV-2 pandemic. The aim of this study was to explore the resilience of the German primary health care system during the second wave of the pandemic from the perspective of identified interface stakeholders, i.e. repre-sentatives of hospitals, district offices and medical associations. Qualitative data from interviews and focus groups were analyzed according to a resilience framework. Main findings include a gap in knowledge transfer, unstructured allocation of responsibilities, and a resulting unregulated flow of patients. Social brokers supported care coordination and knowledge transfer. The response of the capacity to cope with uncertainties was slow and chaotic at the system level, and heterogeneous at the individual level. Building on previous relationships fostered a func-tioning communication, while competition in primary care was identified as a barrier to resilience. As a conclusion, implications for further research and for strengthening resilience of primary care can be derived based on this study.